The nematode parasite fauna in three odontocete species: Phocoena phocoena, Lagenorhynchus albirostris, Lagenorhynchus acutus from Northern Scotland and its relationships with diet composition - Cirillo, Lucia (Alma Mater Studiorum - Università di Bologna, 2015)
Food items and nematode parasites were identified from the stomachs of 42 individuals of Phocoena phocoena, 6 of Lagenorhynchus acutus and 8 of L. albirostris stranded off the coastal waters of Northern Scotland between 2004 and 2014. Post-mortem examinations have revealed heavy parasitic worm burdens. Four nematode species complex as Anisakis spp., Contracaeucum spp., Pseudoterronova spp., and Hysterothylacium spp. were recorded. Data on presence of the anisakid species in cetaceans, reported a significative relationship between the presence of Hysterothylacium and the month of host stranding; suggesting a decrease of larval H. aduncum abundance in the period between April and August due to a seasonal effect related to prey availability. Similarly, the parasite burden of the all anisakid genera was related to the year fraction of stranding, and a relationship statistically significant was found just for L. albirostris with an increase between April and October. This finding is explained by a seasonality in occurrence of white-beaked dolphins, with a peak during August, that might be related to movements of shared prey species and competition with other species (Tursiops truncatus). Geographical differences were observed in parasites number of all anisakid species, which was the highest in cetaceans from the East area and lowest in the North coast. The parasites number also increased significantly with the length of the animal and during the year, but with a significant seasonal pattern only for P. phocoena. Regarding diet composition, through a data set consisting of 34 harbour porpoises and 1 Atlantic white-sided dolphins, we found a positive association between parasite number and the cephalopods genus Alloteuthis. This higher level of parasite infection in squid from this area, is probably due to a quantitative distribution of infective forms in squid prey, an abundance of the final host and age or size maturity of squid.